2012
DOI: 10.1128/jcm.01479-12
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Blood Culture Isolates Directly from Positive Blood Cultures by Use of Matrix-Assisted Laser Desorption Ionization–Time of Flight Mass Spectrometry and a Commercial Extraction System: Analysis of Performance, Cost, and Turnaround Time

Abstract: M atrix-assisted laser desorption ionization-time of flight (MALDI-TOF) mass spectrometry (MS) has been routinely used for the identification of bacteria and fungi from agar culture in many centers in Europe and is increasingly used in North America and elsewhere for primary identification of microorganisms (1, 2, 25). MALDI-TOF instruments use an ionizing laser to vaporize the abundant structural elements (primarily ribosomal proteins) of bacteria and yeasts and analyze the weight and relative abundance of ea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
127
0
9

Year Published

2013
2013
2017
2017

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 179 publications
(147 citation statements)
references
References 25 publications
11
127
0
9
Order By: Relevance
“…The result of one strain of E.coli, that was cultured four-times, and identified correctly in all cases, indicates the robustness of the method. The reported identification rates with MALDI-TOF MS directly from positive blood cultures ranged from 66 to 85.2% for monomicrobial blood cultures, which is lower compared with the 100% identification found using the LC-MS/MS method [9,[23][24][25][26].…”
Section: Bsi Is An Important Cause Of Illness and Deathsmentioning
confidence: 83%
“…The result of one strain of E.coli, that was cultured four-times, and identified correctly in all cases, indicates the robustness of the method. The reported identification rates with MALDI-TOF MS directly from positive blood cultures ranged from 66 to 85.2% for monomicrobial blood cultures, which is lower compared with the 100% identification found using the LC-MS/MS method [9,[23][24][25][26].…”
Section: Bsi Is An Important Cause Of Illness and Deathsmentioning
confidence: 83%
“…22 Exemplifying this, previously technically-challenging identification of microorganisms from sputum of cystic fibrosis patients, 8 utilizing multiple selective media and prolonged incubation, may now be completed within 48 hours of sampling. 23 More specifically, a 2012 Canadian study 24 reported a mean reduction in turnaround time of 34.3 hours when definitive identification of isolates directly from blood samples was possible, albeit that this reduction was lower, but still clinically important, at 26.5 hours when incubation was necessary before MALDI-TOF MS could be utilized. These advances are especially relevant clinically as identification of Gram-negative and Gram-positive bacteria as well as yeasts can now be obtained directly from 7-8 ml of blood when using systems such as the MALDI Sepsityper ® Kit (BrukerDaltonics 2010), thereby eliminating incubation times associated with growth on solid media (Fig.…”
Section: Can Laboratory Results Be Expedited?mentioning
confidence: 99%
“…El estudio de Lagacé-Wiens y colaboradores 41 , mediante el uso del kit de preparación de la muestra Sepsityper ® (Bruker Daltonik GmbH, Bremen, Alemania) y análisis por MALDI Biotyper ® de 61 hemocultivos monomicrobianos y dos hemocultivos polimicrobianos encontró una concordancia del 95,1% frente a los métodos convencionales; con una reducción del tiempo promedio del resultado de 34,3 horas en un escenario ideal y de 26,5 horas en una situación más práctica en la que los microorganismos requieren subcultivos y pruebas adicionales para su caracterización definitiva. Un meta-análisis publicado recientemente, que incluyó 21 artículos de investigación que evaluaron el desempeño del estuche Sepsityper ® en el sistema de espectrometría de masas Microflex Biotyper ® , encontró un porcentaje global de identificación correcta a nivel de especie en el 80% de 3320 botellas de hemocultivo positivo.…”
Section: Sangreunclassified